ANALISIS SEDIAAN FOOT SPRAY EKSTRAK ETANOL DAUN BELIMBING WULUH TERHADAP BAKTERI Staphylococcus aureus - Fatayati, Imma; Farwa, Syalsabilla; Tumpuk, Sri; Wahdaniah, Wahdaniah (Jurnal Laboratorium Khatulistiwa, 2025)
The appearance of foot odor is due to the emergence of sweat in the apocrine glands which contain organic ingredients such as the amino acid leucine. Bacteria on the feet have the degrading enzyme leucine dehydrogenase which will degrade the amino acid leucine in sweat into isovaleric acid which is an odorous compound. Foot spray is a foot odor removal product that dries faster and is easier to use. Starfruit leaves contain alkaloids, flavonoids, saponins, tannins and terpenoids as antibacterials. This research aims to explain the size of the inhibition zone formed in five formulas to inhibit Staphylococcus aureus bacteria. This research uses a Quasi Experiment design. The sample used was foot spray of starfruit leaf extract with five treatments, namely formula I (concentration 10%), formula II (concentration 20%), formula III (concentration 30%), formula IV (concentration 40%) and formula V (concentration 50%) with 5 replications so that the number of samples used was 25 samples which were tested for strength against Staphylococcus aureus using the diffusion method. Based on the results of the inhibition test, the inhibition zone formed in formula I was an average of 9.2 mm (moderat), formula II was 10.6 mm (moderat), formula III was 11.4 mm (stronge), formula IV was 12 mm (stronge) and formula V was 12.6 mm (stronge). From the results Friedman test, it was found that p value = 0.002 < α 0.05 so that there were differences in foot spray preparations of ethanol extract of starfruit leaves formulas I, II, III, IV and V against Staphylococcus aureus.